If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -4 = -3(x + -1(-1)) Reorder the terms: -4 + y = -3(x + -1(-1)) Multiply -1 * -1 -4 + y = -3(x + 1) Reorder the terms: -4 + y = -3(1 + x) -4 + y = (1 * -3 + x * -3) -4 + y = (-3 + -3x) Solving -4 + y = -3 + -3x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + y = -3 + 4 + -3x Combine like terms: -4 + 4 = 0 0 + y = -3 + 4 + -3x y = -3 + 4 + -3x Combine like terms: -3 + 4 = 1 y = 1 + -3x Simplifying y = 1 + -3x
| 11x+6-7+5x=17 | | 2-2x*lnx=0 | | 3t+4=40 | | X+(x-1)=1 | | 3x+12=8+2x | | gr+5n=yf | | 2x*lnx+x=2 | | 9(a+b)9a+x= | | 2x-2.3=x-107 | | 8x+3.5=-7x+-2.1 | | 5(4x+7)=15 | | 0=2(n/5)-6(4n-2) | | a^4+2a^3-a^2-20= | | x-(0.06*x)=50000 | | 8/3x3 | | m^6-729= | | -3(4x+9)=-171 | | (8/3)(3) | | 1-2a^3+a^6= | | y=-3x+45 | | 6(8-7x)=6 | | pq+5=13forp | | 99.2/6.2 | | y=3x-45 | | t=3(3a+4)(3a+4) | | -5(-6x+9)=255 | | (6p-24)+9=23 | | 20-x=6x+6 | | a^2x^3-a^2y^3+2ax^3-2ay^3= | | 3(-2x-6)=-78 | | 4x+3.4=5x-1.1 | | -2x-2x=16 |